The Use of Language in Keynote Address on Thai Language and Literature by Prime Minister of Thailand: Case Study of M.R. Kukrit Pramoj and Mr. Chuan Leekpai - Tonpradit, Rungroj; Sriyabhaya, Warawat; Yingyongsak, Warunya; Pothi, Parichart (Chophayom Journal, 2023)
This study aims to analyze the use of language in Keynote Address on Thai language and literature of M.R. Kukrit Pramoj and Mr. Chuan Leekpai and to synthesize the uniqueness and identity of language use in Keynote Address on Thai language and literature by M.R. Kukrit Pramoj. and Mr. Chuan Leekpai by selecting a speech on Thai language and literature of the two people, 1 chapter each, and then analyzing it mainly from the text. According to the theory of words and phrases that the researcher has synthesized. The results of a study of M.R.Kukrit Pramoj’s keynote address on Thai language and literature found that the use of nouns, pronouns, conjunction, suffixes, and transliteration. Chuan Leekpai’s discourse on Thai language and literature found the use of nouns, pronouns, conjunctions, simile, and local languages. Synthesis of the uniqueness and identity of language use in Keynote Address on Thai language and literature by M.R. Kukrit Pramoj. and Mr.Chuan Leekpai found that appeared to use words and phrases that show the common characteristics of the two people. In the use of language found the use of words and phrases in 3 characteristics that are the same consisting of the use of nouns, pronouns, and the use of conjunctions. It was found that the use of Common Noun, Proper Noun, Personal Pronoun, and the use of many conjunctions regarded to the identity of the use of language, it was found that M.R.Kukrit Pramoj used words and phrases that were characterized by the use of conjunctions including the use of many polite endings and the use of English transliteration to accompany the speech. Mr.Chuan Leekpai’s speech is different from M.R.Kukrit’s speech because M.R. Kukrit used content from literature obviously. Chuan Leekpai’s speech was about local dialects. Therefore, the content of Mr.Chuan Leekpai provided examples of local dialects, especially the Southern dialects to describe and references to well-known people in society. There was the use of idioms and metaphor, with and without word of comparison for gaining the weight of speech to persuade the audience to see the importance of the dialect better. Keywords: Uniqueness, Identity, Language, Keynote Address, Thai Prime Minister